Inactivated Rabies Virus Vectored MERS-Coronavirus Vaccine Induces Protective Immunity in Mice, Camels, and Alpacas - Chi, Hang; Wang, Yanqun; Li, Entao; Wang, Xiwen; Wang, Hualei; Jin, Hongli; Han, Qiuxue; Wang, Zhenshan; Wang, Xinyue; Zhu, Airu; Sun, Jing; Zhuang, Zhen; et al. (Frontiers in Immunology, 2022)
Middle East respiratory syndrome coronavirus (MERS-CoV), is an emergent coronavirus that has caused frequent zoonotic events through camel-to-human spillover. An effective camelid vaccination strategy is probably the best way to reduce human exposure risk. Here, we constructed and evaluated an inactivated rabies virus-vectored MERS-CoV vaccine in mice, camels and alpacas. Potent antigen-specific antibody and CD8+ T cell responses were generated in mice, moreover, the vaccination reduced viral replication and accelerated virus clearance in MERS-CoV infected mice. Besides, protective antibody responses against both MERS-CoV and rabies virus were induced in camels and alpacas. Satisfyingly, the immune sera showed broad cross-neutralizing activity against the three main MERS-CoV clades. For further characterizing the antibody response induced in camelids, MERS-CoV-specific variable domains of heavy-chain-only antibody (VHHs) were isolated from immunized alpacas, and showed potent prophylactic and therapeutic efficacy in Ad5-hDPP4-transduced mouse model. These results highlight the inactivated rabies virus-vectored MERS-CoV vaccine as a promising camelids candidate vaccine.